Analyzing Product Quality, Price, Promotion, and Service Quality Impact on Consumer Satisfaction: Es Teh Indonesia Bogor - Haidar, Abdullah; Octaviani, Nadila; Hendrasto, Nur (Universitas Airlangga, 2025)
This study aims to determine the extent to which product quality, price, promotion, and service quality significantly influence customer satisfaction at Es Teh Indonesia in Bogor. A total of 430 respondents participated in this study, with questionnaires distributed using a non-probability sampling technique in a descriptive quantitative research design. Data were analyzed using SPSS 29 software, applying multiple linear regression with an error value of α = 0.05. The results indicate that (1) customer satisfaction is positively and significantly influenced by product quality, (2) price significantly and favorably affects customer satisfaction, (3) promotion significantly and positively impacts customer satisfaction, and (4) service quality also has a positive and significant impact on customer satisfaction. Furthermore, the study finds that product quality, price, promotion, and service quality collectively have a positive and significant influence on customer satisfaction at Es Teh Indonesia in Bogor. These findings underscore the importance of each marketing element in fostering customer loyalty and satisfaction. The research has significant implications for Es Teh Indonesia’s strategy to enhance its product offerings, improve service quality, and design effective promotional campaigns. These results can guide the company's marketing practices to achieve a competitive advantage in the local beverage market